The Camera and the Press - Dinius, Marcy J. (University of Pennsylvania Press, 2012)
Through a wide-ranging examination of antebellum images and literature, The Camera and the Press shows how Americans' first encounter with photography was more textual than visual. This thoroughly illustrated case study reexamines current theories on new media and reconnects print and visual culture in nineteenth-century America.
Description based on publisher supplied metadata and other sources
Keywords: Presse; Daguerreotypie; Öffentliche Meinung; Drucken; Literatur; Fotografie